Gauntlgrym - Salvatore, R. A. 1959- (Salvatore, R. A., 1959- Neverwinter ;, 2010)
Drizzt joins Bruenor on his quest for the fabled dwarven kingdom of Gauntlgrym, but before they even get close, another drow and dwarf pair -- Jarlaxle and Athrogate -- stumbles across it first -- and set into motion a catastrophe that could spell disaster for the unsuspecting people of the city of Neverwinter.